Development of Green Housing Willingness to Pay Conceptual Model on Jabodetabek Community - Pangaribuan, Evonella; Yuniaristanto, Yuniaristanto; Zakaria, Roni (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2023)
The need for housing for Indonesian people is increasing yearly due to the high population growth rate. This fact can gradually trigger global warming. There is a need for intervention in the residential sector to minimize the resulting negative impacts by developing a green building concept. This study uses an extended Theory of Planned Behavior to identify the factors influencing purchase intention and willingness to pay for green housing (GH) in the Jabodetabek community. The study collected 347 valid responses through a survey with a purposive sampling method and used structural equation modeling to test the hypotheses. The factors raised in this study are attitudes, perceived behavioral control, subjective norms, environmental concern, subjective knowledge, policy, perceived risks, green communication, green purchase intentions (GPI), and willingness to pay (WTP). This research proves that attitude, policy, and subjective knowledge factors significantly directly affect GPI. Meanwhile, environmental concerns and subjective knowledge can also significantly and indirectly affect GPI. This study also proves a significant influence between GPI and WTP for GH in the Jabodetabek community. Perceived risk has a significant negative impact on the GPI. Additionally, developers can employ a strategy that combines attitude, subjective knowledge, and environmental concern to design programs that address consumers' cognitive and affective aspects. The government can also play a role in promoting the use of GH through incentives related to green construction.